Pedagogical Support for Responsible Conduct of Research Training - Anderson, Misti Ault (The Hastings Center report, 2016)
The number of training programs for the responsible conduct of research (RCR) has increased substantially over the past few decades as the importance of research ethics has received greater attention. It is unclear, however, whether the proliferation of RCR training programs has improved researcher integrity or the public's trust in science. Rather than training researchers simply to comply with regulations, we could use the opportunity to develop researchers' ability to understand and appreciate the ethical ideals that inform the regulations in order to help them integrate ethical decision-making into their work on a regular basis. Incorporating ethical principles into research training requires a new way of teaching RCR and the development of support materials to facilitate its adoption. The Presidential Commission for the Study of Bioethical Issues, a panel established to advise the President on bioethical issues arising from advances in biomedicine and related areas of science and technology, developed and provides pedagogical materials based on its published reports to facilitate the integration of ethics education across the curriculum and in support of RCR and general bioethics education.